A qualitative, interpretive study exploring the well-being of slaughterers : a comparison between Jewish, Muslim and secular slaughterers - Durr, Elna (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.